A Semantic-Functional Examination of Forms, Expressing Futurity in Classical Armenian - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2022)
A semantic-functional analysis of the three main forms (subjunctive mood, present indicative, and the construction -ոց participle + եմ auxiliary), expressing futurity in Classical Armenian, based on the Bible text in comparison with the Greek original, leads us to the following main conclusions: a) the use of the present indicative in the meaning of the future tense in Classical Armenian is partly accounted for by the general typological tendency for the present indicative to express secondarily the meaning of immediate and/or inevitable future in most languages of the world, and partly, by a growing inner-systemic tendency in Old Armenian for the present indicative to replace the subjunctive mood in all its functions, including the use in future indicative sense. Therefore, the meaning of the Greek future tense is often conveyed through the present indicative in Armenian; b) nevertheless, the subjunctive mood still continues to function as the most frequent way to express futurity in Classical Armenian, so that not only the Greek future tense but also the present indicative (when the latter is used in the meaning of immediate and/or inevitable future) are often rendered by the subjunctive mood in Classical Armenian; c) as to the semantic-functional peculiarities of the analytical future construction -ոց participle + եմ auxiliary, it expresses, depending on the context, three main nuances of meaning: an expected future (or predestined future); the necessity or inevitability of the future action/event to be fulfilled; and the intention to do something.
Keywords: Classical Armenian; futurity; the analytical future construction; subjunctive mood; a semantic-functional analysis; an expected future (predestined future)